Noncognitive Abilities and Financial Distress: Evidence from a Representative Household Panel - Parise, Gianpaolo; Peijnenburg, Kim (Review of Financial Studies, 2019)
This paper provides evidence of how noncognitive abilities affect financial distress. In a representative panel of households, we find that people in the bottom quintile of noncognitive abilities are 10 times more likely to experience financial distress than those in the top quintile. We provide evidence that this relation largely arises from worse financial choices and lack of financial insight by low-ability individuals and reflects differential exposure to income shocks only to a lesser degree. We mitigate endogeneity concerns using an IV approach and an extensive set of controls. Implications for policy and finance research are discussed. Received September 24, 2017; editorial decision September 26, 2018 by Editor Stijn Van Nieuwerburgh. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.